The contribution of selected variants in ACE, MSTN and ADRB2 genes in the achievements of judo practitioners - Kwasniak, K.; Myszka, A.; Czarnik, J.; and Tabarkiewicz, J. (Archives of Budo, 2018)
Background and Study Aim: I/D polymorphism of the ACE gene is one of the best known genetic variants which affects physical performance in humans. These polymorphisms act on the RAS, affecting the body's water and sodium balances. Another variant of genes which can play an important role in predisposition to sport engagement are Arg16Gly and Gln27Glu of the ADRB2 gene and K153R of the MSTN gene. ADRB2 is expressed on bronchial smooth muscle and is associated with lipid metabolism; in turn MSTN modulates myoblast proliferation and hence muscle mass and strength. The aim of this study was the question of whether selected gene variants (I/D, Arg16Gly, Gln27Glu, and K153R polymorphisms in the ACE, ADRB2, and MSTN genes, respectively) have a relationship with achievements obtained by competitive judo athletes and their predisposition to injuries.